-5x-10=-7x+6

Simple and best practice solution for -5x-10=-7x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-10=-7x+6 equation:


Simplifying
-5x + -10 = -7x + 6

Reorder the terms:
-10 + -5x = -7x + 6

Reorder the terms:
-10 + -5x = 6 + -7x

Solving
-10 + -5x = 6 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-10 + -5x + 7x = 6 + -7x + 7x

Combine like terms: -5x + 7x = 2x
-10 + 2x = 6 + -7x + 7x

Combine like terms: -7x + 7x = 0
-10 + 2x = 6 + 0
-10 + 2x = 6

Add '10' to each side of the equation.
-10 + 10 + 2x = 6 + 10

Combine like terms: -10 + 10 = 0
0 + 2x = 6 + 10
2x = 6 + 10

Combine like terms: 6 + 10 = 16
2x = 16

Divide each side by '2'.
x = 8

Simplifying
x = 8

See similar equations:

| 4-6x=4+6x | | 10x+2=4(2x-3) | | 8m-2=-3 | | 2.5(10x+8)+3x= | | 10x-2=4(2x-3) | | 2n*n-5=3n*n^2*n*4 | | 4x^3+5x^2-18x+9=0 | | 3.5x+215=495 | | 30/y=6/1/5 | | 2(3x-7)-10=20 | | -4x-118=116+9x | | 21+x=-39 | | 2[7-5(1-x)]+6x=-12+3[6(x+1)-3x] | | -3.7t-4.1=6.3t+6 | | 21+x=-31 | | 3x+100=4x+x | | X+3=y-5 | | (x+7)+(2x-1)+(2x+3)=79 | | 3n+n+5=37 | | (12y+9x)-(x-y)= | | -3(5s-6)-18=-3(7s+2)-3 | | 3/4x2=21 | | 5X/6-3/8=7X/4 | | 16x-1024/x2 | | 4(n-25)=9n | | 18000+36000r+18000r^2=0 | | 100-207/8 | | 24.6176=3.14r^2 | | 4x-12=7+7x-4 | | 0.8=5.8/x | | 1.2x+5=3.4 | | 2x^3+3x^2-29x-60=0 |

Equations solver categories